DriftScalarDyFoam: An OpenFOAM-Based Multistage Solver for Drifting Snow and Its Distribution Around Buildings - Chen, Xiaoxiao; Yu, Zhixiang (Frontiers in Earth Science, 2022)
There is a complex coupling relationship between airflow and snow cover. In a period of hours or even days, the airflow will cause the redistribution of snow, and the redistribution of snow will cause the airflow to change. This paper develops a dynamic mesh technology applied in snow drifting simulation, through real-time dynamic mesh update to depict the snow surface evolution process under long-period snow drifting, and a solver application named driftScalarDyFoam based on OpenFOAM is implemented. This solver divides the long-period snow drifting process into several stages, in each of which a snow transport equation is applied to predict the spatial distribution of snow and finally the snow surface evolves according to the erosion-deposition model. This method we proposed has been validated for several measured cases including snow distribution on a flat roof and snow distribution around the building.